Dynamical control of topological unidirectional guided resonances via external magnetic field - Bao Jie Zheng; Wei Jie Shi; Hui Yuan Dong; Yong Tao Li; Jia Qi Li; Zheng-Gao Dong; Jin Wang (Physical Review Research)
Asymmetric radiation in upward and downward directions supported by leaky modes can be generally exhibited in the reciprocal but geometrical up-down mirror-symmetry-breaking structures, i.e., photonic crystal slabs. Here, we theoretically propose and numerically demonstrate a scheme to break the reciprocity, and to generate and manipulate the unidirectional guided resonances (UGRs) in a one-dimensional magneto-optical (MO) grating, which radiate solely toward one side with no emission in the opposite direction. Under an external magnetic field, it is found that genuine UGRs (or quasi-UGRs) in topological nature, depicted by a phase winding number of far-field radiation, can be created by hybridizing the different orthogonal bands in such a nonreciprocal grating. We further investigate the evolution, annihilation, and band transition for residential position of UGRs in three-dimensional parameter space, and we also notice that the emission direction may be switched from one side to the other due to the tuning of the asymmetric coupling. Finally, the excitation of UGRs is examined in a lossless system related to directional coupling of external waves, and it can also be utilized to realize perfect absorption in a lossy MO grating structure under single-sided illumination. The general principles presented here may lead to an efficient and active approach for the dynamic manipulation of topological radiation asymmetry, and they may serve as new inspiration to control flexibly the resonant and topological properties of light-matter interactions.